Increasing the design efficiency of roads in Al-Shatrah city center by achieving adequacy for car parking - Rezaq Ali Al-Timimy, Sophia; Abdul Hussein Bedewy, Baydaa; كريم جمعة, يقين (Journal of Planner and Development, 2023)
The research deals with the analysis of the city's commercial center using geographic information systems to solve the problem of congestion by evaluating the efficiency and adequacy of car parking lots according to local and Arab standards. Undoubtedly, the importance of car parking areas, as they are not within the desired efficiency within the city, will lead to congestion and traffic becomes very difficult. Thus, the transportation service loses its most important characteristic, which is the ease of movement. Therefore, there has become an urgent need to study and analyze it, as well as to verify the adequacy of the service, and the amount of deficit required to be provided to solve the transportation crisis and ease of traffic in the city center. For all that, the commercial center was chosen because it is the most crowded in the city of Al-Shatrah, to prepare a traffic study that includes collecting data on the locations and numbers of vehicles parked on both sides of the street, and analyzing the study area and its location besides ownership and prices. Therefore, the research methodology deals with descriptive analysis, which includes an analytical study of car parking lots within Arab and local standards, and comes up with analytical indicators, then the practical side deals with quantitative analysis represented by numbers of car parking lots, especially at rush hour, and then using (spatial analysis) based on the satellite image. As well as making a questionnaire and using statistical analysis represented by the normal distribution with binomial to analyze the results through the zero hypotheses and access to the actual need from the field survey and geographic information systems for car parks amounting to (252) car–parking spaces, which is greater than the available capacity .